Manajemen Produksi dan Pemasaran Benih Padi di PT. PERTANI (Persero) Cabang Bali - CAHYANINGRUM, MADE CANDRA KIRANA; SUAMBA, I KETUT; SURYAWARDANI, I GUSTI AYU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.1, Januari 2018DO - 10.24843/JAA.2018.v07.i01.p02, 2018)
The Production and Marketing Management of Rice Seeds at PT. PERTANI (Limited) of Bali Branch This study aimed at determining the application of management functions in the production of rice seeds in PT. PERTANI (Limited) of Bali Branch, as well as to find out the marketing activities of rice seed conducted by PT. PERTANI (Limited) of Bali Branch. Based on these objectives, the study used qualitative descriptive analysis method. The result of the research showed that PT. PERTANI (Limited) of Bali Branch has implemented management function well in production activities. Implementation of management functions include the planning process that has been set in the Work Plan and Corporate Budget, the organizing process was set in a clear organizational structure. Monitoring process in production activities was conducted by the head of Seed Production Unit (UPB) of Munggu and team. The evaluation process was conducted every three months starting from the amount of production, the basic cost of the seeds, and the costs incurred in the production activities, and the quality of the seeds produced by PT. PERTANI (Limited) of Bali Branch that has implemented marketing mix (4P) items consisting of product, place, price, and promotion in marketing the seeds.